Processing of discarded refrigerators in The Netherlands - Stoop, Mat L.M.; Lambert, Alfred J. D.
The authors suggest that the re-design of refrigerators in The Netherlands could be modified to cover re-processing of discarded refrigerators with a view to ecological considerations. The work is based on a case study.
Based on a case study, it is shown that the introduction of new technology does not always turn out well when, because of social pressure, policy makers take ad hoc decisions based on short-term interests. They do not take sufficient time to think about the matter extensively. This paper describes some aspects of scrapping domestic refrigerators. It shows that recycling of refrigerators should be based on an integral approach, aiming at maximum elimination of CFCs, optimal recovery of metals and low input of energy. Using this approach, the present Dutch emission of greenhouse gases can be reduced by 0.3-0.4 percent. The required technology is directly available and the costs are much lower than those of the more usual CO2-saving measures.
Keywords: Discarded refrigerators--Netherlands.